A composite positive electrode material for lithium battery and preparation method thereof

Through the preparation of FeS2-doped Cr8O21 composite positive electrode material, the processing difficulty and discharge performance problems of block Cr8O21 in lithium batteries are solved, forming a powdered material with small particle size and high purity, which improves the discharge efficiency and electrochemistry of lithium batteries. Performance and simplify the preparation process.

CN118833859BActive Publication Date: 2025-01-07SHANGHAI INST OF SPACE POWER SOURCES
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411277540.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-12
Publication Date
2025-01-07
Estimated Expiration
2044-09-12

AI Technical Summary

Technical Problem

The block Cr8O21 material has problems such as difficult processing and poor discharge performance in lithium batteries, and its high-temperature decomposition process strictly requires temperature and time, which limits its application.

Method used

The preparation method of FeS2-doped Cr8O21 composite positive electrode material is adopted. By grinding CrO3 and FeS2, the temperature is controlled at 260~270℃ to form a powdery Cr8O21 with a small particle size and high purity coated FeS2 structure to reduce by-products generate.

Benefits of technology

It significantly improves the discharge efficiency and electrochemical performance of lithium batteries, reduces the difficulty of material processing, and makes the preparation process more controllable and simple.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118833859B_ABST
    Figure CN118833859B_ABST
Patent Text Reader

Abstract

The present invention discloses a composite positive electrode material for a lithium battery and a preparation method thereof, the method comprising: a grinding step: grinding CrO3 and FeS2 to a mixture with uniform color; a heating and sintering step: heating the mixture to react to obtain FeS2-doped Cr8O 21 Composite positive electrode material; wherein the mass ratio of CrO3 to FeS2 is (10-20):1, the heating temperature is 260°C-270°C, and the constant temperature time is 8h-18h. 21 Composite positive electrode materials have the characteristics of small particle size, high purity and few impurities. When used in lithium batteries, they can effectively enhance the discharge efficiency and electrochemical performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium batteries, and in particular to a composite positive electrode material for lithium batteries and a preparation method thereof. Background Art

[0002] With the growing global demand for renewable and clean energy, new energy technologies have ushered in opportunities for rapid development. Especially in the fields of portable electronic devices, electric vehicles and smart grids, high energy density energy storage systems have become one of the key technologies. Lithium batteries have become the current mainstream energy storage technology due to their relatively high energy density, long cycle life and good environmental adaptability. However, with the popularization of high energy density electronic devices, the market's performance requirements for lithium batteries continue to increase, especially the pursuit of energy density and power density, prompting researchers to continuously explore new lithium battery electrode materials.

[0003] Lithium batteries are mainly composed of core structures such as positive electrode, electrolyte and negative electrode. 21 As a new type of electrode material, Cr8O has great potential as a positive electrode material for lithium batteries due to its high theoretical specific energy, high voltage platform and high lithium storage capacity. Compared with traditional lithium battery positive electrode materials (lithium cobalt oxide, lithium manganese oxide, lithium iron phosphate, etc.), Cr8O 21 It can provide higher energy output and meet the market demand for higher energy density batteries.

[0004] However, Cr8O 21 There are some challenges in practical application. First, Cr8O 21 Usually in block form, with larger particle size and higher viscosity, it is more difficult to process mechanically (grinding, cutting, etc.). 21 The low crystallinity may cause a large volume change during the charge and discharge process, leading to stress concentration and material rupture, which seriously affects the discharge performance of the material. Secondly, the reaction temperature and time must be strictly controlled to ensure the preparation of high-purity Cr8O by one-step pyrolysis of CrO3. 21 , in order to achieve its best electrochemical performance. These problems greatly limit the 21 In order to overcome the above challenges, Cr8O 21 Material modification has become a hot topic in current research. Summary of the invention

[0005] The purpose of this invention is to solve the problem of blocky Cr8O 21 In order to solve the problems of large particle size, great processing difficulty and poor discharge performance, a method for preparing a composite positive electrode material for lithium batteries is proposed to expand its application range in high energy density lithium batteries.

[0006] In order to achieve the above object, the present invention provides a method for preparing a composite positive electrode material for a lithium battery, the method comprising:

[0007] Grinding step: Grind CrO3 and FeS2 to a mixture of uniform color;

[0008] Heating and sintering step: heating the mixture to react and obtain FeS2-doped Cr8O 21 Composite cathode materials;

[0009] The mass ratio of CrO3 to FeS2 is (10-20):1, the heating temperature is 260°C-270°C, and the constant temperature time is 8h-18h.

[0010] Optionally, before the grinding step, the CrO3 and FeS2 are both dried in advance.

[0011] Optionally, the grinding step is performed in a dry environment, CrO3 and FeS2 are ground separately, and then mixed into a mixture with uniform color.

[0012] Optionally, the heating rate of the heating reaction is 4-6°C / min.

[0013] Optionally, oxygen or air is introduced during the heating reaction.

[0014] Optionally, the method further comprises: performing the grinding step and the heating and sintering step in multiple cycles to complete the reaction.

[0015] The present invention also provides a composite positive electrode material for a lithium battery obtained by the above-mentioned preparation method.

[0016] Optionally, the composite positive electrode material for lithium battery is a powdered solid.

[0017] Optionally, the powdered solid is flake Cr8O 21 Coated with FeS2.

[0018] The beneficial effects of the present invention include:

[0019] 1. For the existing block Cr8O 21 In order to solve the problems of large particle size, greater processing difficulty and poor discharge performance, the present invention introduces FeS2 as a nucleation site during the heating and decomposition process of CrO3 to guide Cr8O 21 Crystallization on its surface, due to the uniform dispersion of FeS2, can form small particle size Cr8O 21 The present invention adopts FeS2 doped Cr8O 21 The composite positive electrode material is macroscopically a powdery solid, and the powdery solid is a flake Cr8O 21At the same time, the present invention unexpectedly found that the heating temperature of 260-270°C limits the Cr8O 21 Continue to generate Cr2O5, Cr5O 12 and Cr2O3 and other by-products, the prepared composite positive electrode material has the characteristics of small particle size, high purity and few impurities.

[0020] 2. FeS2 doped with Cr8O prepared by the present invention 21 When the composite cathode material is used in lithium batteries, during the discharge process of lithium batteries, due to the FeS2 doping Cr8O 21 The composite cathode material is a powdered solid, compared to the bulk Cr8O 21 It has a larger specific surface area, which is more conducive to the full infiltration of the electrolyte and the rapid insertion and extraction of lithium ions, thereby significantly enhancing the discharge efficiency and electrochemical performance of the battery. In addition, the preparation method provided by the present invention also has the advantages of simple process, controllable reaction process and low preparation difficulty, and has good application prospects in the field of lithium batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 This is the thermogravimetric analysis diagram of CrO3.

[0022] Figure 2 Cr8O 21 SEM image of .

[0023] Figure 3 FeS2 doped with Cr8O prepared in Example 1 21 Composite cathode materials and Cr8O 21 XRD pattern of standard pattern.

[0024] Figure 4 FeS2 doped with Cr8O prepared in Example 1 21 SEM image of the composite cathode material.

[0025] Figure 5 FeS2 doped with Cr8O prepared in Example 2 21 SEM image of the composite cathode material.

[0026] Figure 6 FeS2 doped with Cr8O prepared in Example 3 21 SEM image of the composite cathode material.

[0027] Figure 7 FeS2 doped with Cr8O prepared in Example 1 and Comparative Example 2 21 XRD patterns of composite cathode materials and FeS2.

[0028] Figure 8It is a comparison diagram of the discharge voltammetric curves of Examples 1-3 and Comparative Examples 1-3.

[0029] Fig. 9 The figure is a comparison diagram of the discharge voltammetric curves of Example 1 and Comparative Examples 4-5.

[0030] Fig.10 The figure is a comparison diagram of the discharge voltammetric curves of Example 1 and Comparative Examples 6-7. DETAILED DESCRIPTION

[0031] The technical solution of the present invention will be described clearly and completely below in conjunction with the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0032] In the prior art, block Cr8O 21 Usually, it has a larger particle size (3μm-6μm) and higher viscosity. It adheres to the crucible during processing and is difficult to remove, resulting in greater difficulty in mechanical processing and poor material discharge performance. 21 The particle size is reduced, the difficulty of material processing is reduced, and the discharge performance is improved, and FeS2 is designed to be doped with it. Specifically, the present invention provides a method for preparing a composite positive electrode material for a lithium battery, the method comprising:

[0033] Grinding step: Grind CrO3 and FeS2 to a uniform color mixture.

[0034] Before grinding, CrO3 and FeS2 are dried in advance to remove excess moisture, and the grinding process is always carried out in a dry environment to prevent CrO3 and FeS2 from adhering to the mortar after absorbing water. At the same time, CrO3 and FeS2 are ground separately first, and then mixed until the color is uniform to obtain a mixture. It can be understood that grinding separately and then mixing makes the contact area between the two larger and the mixing more uniform.

[0035] Among them, the mass ratio of CrO3 and FeS2 is (10-20):1. When the FeS2 content is higher than the above mass ratio, Cr8O 21 The particle size is smaller and cannot completely occupy the nucleation sites of FeS2, making the Cr8O attached to each FeS2 particle 21 The quantity does not reach the optimal range; when the FeS2 content is lower than the above mass ratio, Cr8O 21 The larger the particle size, the higher the viscosity and the more difficult it is to process. For example, it is difficult to grind and form a powder with a large specific surface area.

[0036] Heating and sintering step: heating the mixture to react and obtain FeS2-doped Cr8O 21 Composite positive electrode materials.

[0037] The heating rate is 4-6℃ / min. When the temperature reaches 200℃, CrO3 gradually melts into liquid, and FeS2 particles are dispersed in the liquid CrO3 as nucleation sites. When the temperature reaches 260℃, CrO3 begins to decompose and the formed Cr8O 21 It is easy to crystallize at the nucleation site. Since the FeS2 particles are evenly dispersed, the formed Cr8O 21 The crystal size is small. At the same time, oxygen or air is introduced during the heating process, which mainly inhibits the decomposition rate of CrO3 and can also make Cr8O 21 The crystal size is small, and it can also inhibit Cr8O 21 Excessive decomposition into Cr2O5, Cr5O 12 In addition, the present invention unexpectedly found that the heating temperature of 260-270°C can also limit the generation of Cr8O 21 Excessive decomposition into by-products, resulting in the formation of Cr8O 21 Higher purity, less impurities. Constant temperature for 8h ~18h can ensure complete reaction.

[0038] The method further comprises: performing the grinding step and the heating sintering step in multiple cycles. Different amounts of CrO3 and FeS2 will result in different number of cycles. When the amount is large, multiple cycles can ensure complete reaction, but in the embodiment of the present invention, the amount is small, so only two cycles are performed.

[0039] The present invention also provides a composite positive electrode material for a lithium battery obtained by the above-mentioned preparation method.

[0040] The composite positive electrode material for lithium battery is macroscopically presented as a powdery solid, and the powdery solid is a flake Cr8O 21 Coated FeS2, compared with bulk Cr8O 21 It has a larger specific surface area, which is more conducive to the full infiltration of electrolyte and the rapid insertion and extraction of lithium ions. When used in lithium batteries, the discharge efficiency and electrochemical performance are stronger.

[0041] The experimental methods used in the following examples were all carried out according to conventional conditions or conditions recommended by the manufacturers unless otherwise specified.

[0042] Thermogravimetric analysis of CrO3 Figure 1 As shown in the figure, when the heating temperature is 260~270℃, CrO3 decomposes to form the main product Cr8O 21 When the heating temperature exceeds 300℃, CrO3 decomposes to form the main product Cr8O 21In addition, there are Cr2O5, Cr5O 12 and Cr2O3 byproducts. This result shows that when the heating temperature is controlled at 260~270℃, the Cr8O 21 Higher purity and less impurities.

[0043] Comparative Example 1

[0044] The positive electrode sheet preparation method for electrochemical testing is as follows:

[0045] Take 240 mg Cr8O 21 , 30 mg of conductive carbon black, 30 mg of polyvinylidene fluoride and 700-800 mg of N-methylpyrrolidone were put into an agate mortar and ground for 15 minutes, and then the evenly ground slurry was coated on aluminum foil. The aluminum foil was placed in a vacuum drying oven and dried for 12 hours at a drying temperature of 100°C. After drying, it was punched into a 14 mm diameter disc using a punching machine to obtain a positive electrode sheet. Cr8O 21 The SEM images are as follows Figure 2 As shown in the figure, it can be seen that Cr8O 21 It shows a typical flake structure. The discharge voltammetric curve of the positive electrode is as follows: Figure 8 shown. Example 1

[0046] Grinding step: 1 g of CrO3 and 0.05 g of FeS2 after drying pretreatment are ground separately in a dry environment and then mixed until the color is uniform to obtain a mixture.

[0047] Heating and sintering step: the mixture is transferred to a normal pressure reactor and placed in a muffle furnace for heating reaction. During the heating reaction, oxygen or air is introduced, and the temperature is increased from room temperature to 270°C at a heating rate of 5°C / min and kept at a constant temperature for 18 hours. After the reaction is completed, the FeS2-doped Cr8O 21 The above grinding step and heating sintering step are repeated for multiple times to complete the reaction. Figure 3 FeS2 doped with Cr8O 21 Composite cathode materials and Cr8O 21 The XRD diagram of the standard spectrum shows that the introduction of FeS2 as a nucleation site can produce Cr8O with higher purity. 21 In addition, FeS2 doped with Cr8O 21 The SEM and XRD patterns of the composite cathode materials are shown in Figure 4 and Figure 7 shown.

[0048] The preparation method of the positive electrode sheet for electrochemical testing is the same as that of Comparative Example 1, except that Cr8O 21 Replaced with FeS2 doped Cr8O 21Composite positive electrode material. The discharge voltammetric curve of the positive electrode sheet is as follows Figure 8 shown. Example 2

[0049] Grinding step: Grind 1 g of CrO3 and 0.1 g of FeS2 after drying pretreatment separately in a dry environment and mix them until the color is uniform to obtain a mixture.

[0050] Heating and sintering step: the mixture is transferred to a normal pressure reactor and placed in a muffle furnace for heating reaction. During the heating reaction, oxygen or air is introduced, and the temperature is increased from room temperature to 260°C at a heating rate of 6°C / min and kept at a constant temperature for 12 hours. After the reaction is completed, the FeS2-doped Cr8O 21 Composite positive electrode material. The above grinding step and heating sintering step are repeated for multiple times to complete the reaction. 21 SEM images of composite cathode materials Figure 5 shown.

[0051] The preparation method of the positive electrode sheet for electrochemical testing is the same as that of Comparative Example 1, except that Cr8O 21 Replaced with FeS2 doped Cr8O 21 Composite positive electrode material. The discharge voltammetric curve of the positive electrode sheet is as follows Figure 8 shown. Example 3

[0052] Grinding step: 1 g of CrO3 and 0.15 g of FeS2 after drying pretreatment are ground separately in a dry environment and then mixed until the color is uniform to obtain a mixture.

[0053] Heating and sintering step: the mixture is transferred to a normal pressure reactor and placed in a muffle furnace for heating reaction. During the heating reaction, oxygen or air is introduced, and the temperature is increased from room temperature to 270°C at a heating rate of 4°C / min and kept at a constant temperature for 8 hours. After the reaction is completed, the FeS2-doped Cr8O 21 Composite positive electrode material. The above grinding step and heating sintering step are repeated for multiple times to complete the reaction. 21 SEM images of composite cathode materials Figure 6 shown.

[0054] The preparation method of the positive electrode sheet for electrochemical testing is the same as that of Comparative Example 1, except that Cr8O 21 Replaced with FeS2 doped Cr8O 21 Composite positive electrode material. The discharge voltammetric curve of the positive electrode sheet is as follows Figure 8 shown.

[0055] Figure 4 Only flake Cr8O 21, FeS2 is wrapped in it and not exposed; when FeS2 is exposed, the contrast between Cr and S will be very large, and the black and white contrast of the particles in the figure will be very obvious, and it is impossible to show the same color depth as shown in the figure. Figure 4-6 It can be seen that with the increase of FeS2 content (the mass ratio of CrO3 and FeS2 is 20:1, 10:1, and 6.7:1, respectively), the flake Cr8O 21 The spherical structure formed by coating FeS2 gradually changes from compact to loose, and the Cr8O 21 The particle size has a trend of decreasing. The particle size is in the range of 400nm-1000nm. When the mass ratio of CrO3 to FeS2 is lower than 10:1, the smaller particle size of Cr8O 21 Unable to fully occupy the nucleation sites of FeS2, the Cr8O attached to each FeS2 particle 21 The number of Cr8O attached to each FeS2 particle did not reach the optimal range. The results show that only when the mass ratio of CrO3 to FeS2 is (10~20):1 21 The quantity can reach the optimal range and the discharge performance of the material is better.

[0056] Comparative Example 2

[0057] Grinding step: 1 g of CrO3 and 0.2 g of FeS2 after drying pretreatment are ground separately in a dry environment and then mixed until the color is uniform to obtain a mixture.

[0058] Heating and sintering step: the mixture is transferred to a normal pressure reactor and placed in a muffle furnace for heating reaction. During the heating reaction, oxygen or air is introduced, and the temperature is increased from room temperature to 270°C at a heating rate of 5°C / min, and the temperature is kept constant for 12 hours. After the reaction is completed, the FeS2-doped Cr8O 21 Composite positive electrode material. The above grinding step and heating sintering step are repeated for multiple times to complete the reaction. 21 The XRD pattern of the composite cathode material is shown in Figure 7 shown.

[0059] Figure 7 FeS2 doped with Cr8O prepared in Example 1 and Comparative Example 2 21 From the XRD diagrams of the composite positive electrode material and FeS2, it can be seen that the characteristic diffraction peaks of FeS2 still exist after the heating reaction in Example 1 (CrO3 and FeS2 mass ratio 20:1) and Comparative Example 2 (CrO3 and FeS2 mass ratio 5:1), and the higher the FeS2 content, the greater the diffraction intensity, indicating that FeS2 is wrapped in the generated Cr8O 21 It is not oxidized by oxidants (CrO3 and oxygen) and has a relatively stable structure.

[0060] The preparation method of the positive electrode sheet for electrochemical testing is the same as that of Comparative Example 1, except that Cr8O 21 Replaced with FeS2 doped Cr8O 21 Composite positive electrode material. The discharge voltammetric curve of the positive electrode sheet is as follows Figure 8 shown.

[0061] Comparative Example 3

[0062] Grinding step: Grind 1 g of CrO3 and 1 g of FeS2 after drying pretreatment separately in a dry environment and then mix until the color is uniform to obtain a mixture.

[0063] Heating and sintering step: the mixture is transferred to a normal pressure reactor and placed in a muffle furnace for heating reaction. During the heating reaction, oxygen or air is introduced, and the temperature is increased from room temperature to 270°C at a heating rate of 5°C / min, and the temperature is kept constant for 12 hours. After the reaction is completed, the FeS2-doped Cr8O 21 The above grinding step and heating sintering step are repeated for multiple times to complete the reaction.

[0064] The preparation method of the positive electrode sheet for electrochemical testing is the same as that of Comparative Example 1, except that Cr8O 21 Replaced with FeS2 doped Cr8O 21 Composite positive electrode material. The discharge voltammetric curve of the positive electrode sheet is as follows Figure 8 shown.

[0065] Figure 8 The discharge voltammetric curves of Examples 1-3 and Comparative Examples 1-3 are compared. It can be seen that pure Cr8O 21 The prepared positive electrode sheet has a discharge capacity of 395 mAh / g. When the mass ratio of CrO3 to FeS2 is ≤5:1, the discharge capacity of the positive electrode sheet prepared by the composite positive electrode material is 250-300 mAh / g, which is significantly lower than that of Examples 1-3 (the discharge capacity is greater than 400 mAh / g). It can be seen that when the mass ratio of CrO3 to FeS2 is (10-20):1, the prepared FeS2 doped with Cr8O 21 When composite positive electrode materials are used in lithium batteries, the discharge efficiency and electrochemical performance are stronger.

[0066] Comparative Example 4

[0067] FeS2 doped Cr8O 21 The preparation method of the composite positive electrode material is the same as that of Example 1, except that the heating temperature of 270°C is replaced by 250°C.

[0068] The preparation method of the positive electrode sheet for electrochemical testing is the same as that of Comparative Example 1, except that Cr8O 21 Replaced with FeS2 doped Cr8O 21Composite positive electrode material. The discharge voltammetric curve of the positive electrode sheet is as follows Fig. 9 shown.

[0069] Comparative Example 5

[0070] FeS2 doped Cr8O 21 The preparation method of the composite positive electrode material is the same as that of Example 1, except that the heating temperature of 270°C is replaced by 300°C.

[0071] The preparation method of the positive electrode sheet for electrochemical testing is the same as that of Comparative Example 1, except that Cr8O 21 Replaced with FeS2 doped Cr8O 21 Composite positive electrode material. The discharge voltammetric curve of the positive electrode sheet is as follows Fig. 9 shown.

[0072] Fig. 9 The discharge voltammetric curves of Example 1 and Comparative Examples 4-5 are compared. It can be seen that the discharge specific capacity of the positive electrode sheet prepared by the composite positive electrode material of Comparative Example 4 (heating temperature 250°C) and Comparative Example 5 (heating temperature 300°C) is significantly lower than that of Example 1. This result shows that when the heating temperature is 260-270°C, FeS2 doped with Cr8O 21 When composite positive electrode materials are used in lithium batteries, the discharge efficiency and electrochemical performance are stronger.

[0073] Comparative Example 6

[0074] MoS2 doped with Cr8O 21 The preparation method of the composite positive electrode material is the same as that of Example 3, except that FeS2 is replaced by MoS2.

[0075] The preparation method of the positive electrode sheet for electrochemical testing is the same as that of Comparative Example 1, except that Cr8O 21 Replaced with MoS2 doped Cr8O 21 Composite positive electrode material. The discharge voltammetric curve of the positive electrode sheet is as follows Fig.10 shown.

[0076] Comparative Example 7

[0077] CoS2 doped with Cr8O 21 The preparation method of the composite positive electrode material is the same as that of Example 3, except that FeS2 is replaced by CoS2.

[0078] The preparation method of the positive electrode sheet for electrochemical testing is the same as that of Comparative Example 1, except that Cr8O 21 Replaced with CoS2 doped Cr8O 21 Composite positive electrode material. The discharge voltammetric curve of the positive electrode sheet is as follows Fig.10 shown.

[0079] Fig.10The discharge voltammetric curves of Example 1 and Comparative Examples 6-7 are compared. It can be seen that the discharge specific capacity of the positive electrode sheets prepared by the composite positive electrode materials of Comparative Example 6 (doped with MoS2) and Comparative Example 7 (doped with CoS2) is less than 200 mAh / g, which is significantly lower than that of Example 1. This result shows that Cr8O 21 The composite positive electrode material prepared by doping FeS2 has stronger discharge efficiency and electrochemical performance when used in lithium batteries, and has unexpected technical effects.

[0080] In summary, the FeS2 doped Cr8O 21 The composite cathode material introduces FeS2 as a nucleation site during the thermal decomposition of CrO3, guiding the Cr8O 21 Crystallization on its surface, due to the uniform dispersion of FeS2, can form small particle size Cr8O 21 The FeS2 doped Cr8O prepared by the present invention 21 The composite positive electrode material is macroscopically presented as a powdery solid, and the powdery solid is a flake Cr8O 21 At the same time, the present invention unexpectedly found that the heating temperature of 260-270°C limits the Cr8O 21 Continue to generate Cr2O5, Cr5O 12 The prepared composite positive electrode material has the characteristics of small particle size, high purity and few impurities. 21 When the composite cathode material is used in lithium batteries, during the discharge process of lithium batteries, due to the FeS2 doping Cr8O 21 The composite cathode material is a powdered solid, compared to the bulk Cr8O 21 It has a larger specific surface area, which is more conducive to the full infiltration of the electrolyte and the rapid insertion and extraction of lithium ions, thereby significantly enhancing the discharge efficiency and electrochemical performance of the battery. At the same time, the preparation method provided by the present invention also has the advantages of simple process, controllable reaction process and low preparation difficulty, and has good application prospects in the field of lithium batteries.

[0081] Although the content of the present invention has been described in detail through the above preferred embodiments, it should be appreciated that the above description should not be considered as a limitation of the present invention. After reading the above content, it will be apparent to those skilled in the art that various modifications and substitutions of the present invention will occur. Therefore, the protection scope of the present invention should be limited by the appended claims.

Claims

1. A method for preparing a composite positive electrode material for a lithium battery, characterized in that: The method includes: Grinding step: Grind CrO3 and FeS2 to a mixture of uniform color; Heating and sintering step: heating the mixture to react and obtain FeS2-doped Cr8O 21 Composite cathode materials; The mass ratio of CrO3 to FeS2 is (10-20):1, the heating temperature is 260°C-270°C, and the constant temperature time is 8h-18h.

2. The method for preparing a composite positive electrode material for a lithium battery according to claim 1, characterized in that: Before the grinding step, the CrO3 and FeS2 are both dried in advance.

3. The method for preparing a composite positive electrode material for a lithium battery according to claim 1, characterized in that: The grinding step is carried out in a dry environment, CrO3 and FeS2 are ground separately and then mixed into a mixture with uniform color.

4. The method for preparing a composite positive electrode material for a lithium battery according to claim 1, characterized in that: The heating rate of the heating reaction is 4-6°C / min.

5. The method for preparing a composite positive electrode material for a lithium battery according to claim 1, characterized in that: Oxygen or air is also introduced during the heating reaction.

6. The method for preparing a composite positive electrode material for a lithium battery according to claim 1, characterized in that: The method further comprises: performing the grinding step and the heating and sintering step in multiple cycles to complete the reaction.

7. A composite positive electrode material for a lithium battery obtained according to the preparation method of claims 1-6.

8. The composite positive electrode material for lithium battery according to claim 7, characterized in that: The composite positive electrode material for lithium battery is a powdery solid.

9. The composite positive electrode material for lithium battery according to claim 8, characterized in that: The powdered solid is flake Cr8O 21 Coated with FeS2.

Citation Information

Patent Citations

  • Method for easily synthesizing chromium oxides

    CN108609656A

  • Chromium oxide composite material added with activating agent as well as preparation method and application of chromium oxide composite material

    CN115188918A